-6+b=-8

Simple and best practice solution for -6+b=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+b=-8 equation:


Simplifying
-6 + b = -8

Solving
-6 + b = -8

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + b = -8 + 6

Combine like terms: -6 + 6 = 0
0 + b = -8 + 6
b = -8 + 6

Combine like terms: -8 + 6 = -2
b = -2

Simplifying
b = -2

See similar equations:

| 7-5(1+4r)=-36 | | 3+2y*15=38 | | 2x+3y+5z=160 | | 10m^8/5m^9 | | 4w-14=6 | | -27-7v=8(6v-5) | | u+8=16 | | Z+2y+x=38 | | 26=-8+7(n-9) | | 7x-8=-6x+3x-2 | | p=312(1+0.015)2011 | | -67=6k-1 | | p=312(1+0.015)t | | V/8-6=8 | | 5x-1/3=3 | | 30x-60+3=30 | | 6n(3n-5)= | | 8.4a+13=105 | | 20=-3y+6y | | 6(3x-8)-3=6(x-4)+45 | | 39=3v-15 | | 2[5x+3]=26 | | -h+3=-h+9 | | 2[5x-3]=26 | | -12=4+5u | | 1x+5=1x-2 | | P=0.258 | | 7(9z+8)=-24+5z | | 0.5(x^4+3)+19= | | 2x-3(x+4)=9-(3+2x) | | 15,6/2,88=x/14,40 | | 2(3x-1)=-50 |

Equations solver categories